Respuesta :
1. No answer ( may be due to incorrect question)
2. x = -3
y = 4
3. x= 4
y = 2
4.x = -63/40
y= -19/20
Step 1
Multiply equation 1 by the coefficient of x in equation 2
Multiply equation 2 by the coefficient of x I'm equation 1
(after completing this step you will derive equation 3 and 4 )
Step 2
Subtract equation 4 from equation 3
Step 3
Divide both sides of the equation by the coefficient of y
Step 4
substitute your value for y in equation 1 or 2
(after this you will derive the values of x)
Note : This method is for the Elimination of x
I hope it helps
![Ver imagen Аноним](https://us-static.z-dn.net/files/d63/3546783e9b8fd3ef47bcfe0c41ba18e5.jpg)
![Ver imagen Аноним](https://us-static.z-dn.net/files/d94/7639f580f791b400e190d74bb6004477.jpg)